African and Asian Mitochondrial DNA Haplogroups Confer Resistance Against Diabetic Stresses on Retinal Pigment Epithelial Cybrid Cells In Vitro - Dolinko, Andrew H.; Chwa, Marilyn; Atilano, Shari R.; Kenney, M. Cristina (Molecular neurobiology, 2020)
Diabetic retinopathy (DR) is the most common cause of blindness for individuals under the age of 65. This loss of vision can be due to ischemia, neovascularization, and/or diabetic macular edema, which are caused by breakdown of the blood–retina barrier at the level of the retinal pigment epithelium (RPE) and inner retinal vasculature. The prevalence of diabetes and its complications differ between Caucasian-Americans and certain minority populations, such as African-Americans and Asian-Americans. Individuals can be classified by their mitochondrial haplogroups, which are collections of single nucleotide polymorphisms (SNPs) in mitochondrial DNA (mtDNA) representing ancient geographic origins of populations. In this study, we compared the responses of diabetic human RPE cybrids, cell lines containing identical nuclei but mitochondria from either European (maternal European) or maternal African or Asian individuals, to hypoxia and high glucose levels. The African and Asian diabetic ([Afr+Asi]/DM) cybrids showed (1) resistance to both hyperglycemic and hypoxic stresses; (2) downregulation of pro-apoptotic indicator BAX ; (3) upregulation of DNA methylation genes, such as DNMT3A and DNMT3B ; and (4) resistance to DNA demethylation by the methylation inhibitor 5-Aza-2′-deoxycytidine (5-Aza-dC) compared to European diabetic (Euro/DM) cybrids. Our findings suggest that mitochondria from African and Asian diabetic subjects possess a “metabolic memory” that confers resistance against hyperglycemia, hypoxia, and demethylation, and that this “metabolic memory” can be transferred into the RPE cybrid cell lines in vitro.